2013
DOI: 10.1007/s11238-013-9407-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of intuition and reasoning in driving aversion to risk and ambiguity

Abstract: Using information on a large sample of retail investors and experimental data we find that risk aversion and risk ambiguity are correlated: individuals who dislike risk also dislike ambiguity. We show that what links these traits is the way people handle decisions. Intuitive thinkers are less averse to risk and less averse to ambiguity than individuals who base their decisions on effortful reasoning. We confirm this finding in a series of experiments. One interpretation of our results is that the high-speed of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 57 publications
6
29
0
Order By: Relevance
“…Yet, their three-category classification is based on a small sub-sample of their data, consisting of only 38 students. 10 The non-incentivized version of the Ellsberg urn experiment with five answer possibilities shows a somewhat smaller fraction of ambiguity neutral subjects compared to Butler et al (2013). The results for the subjects' willingness to pay for complementary temperature lottery tickets are qualitatively similar to Fox and Tversky (1995), although their average relative ambiguity premium is with 39% around twice as large as in our experiment that exhibits an average relative ambiguity premium of 20%.…”
Section: Aggregate Consistencymentioning
confidence: 54%
See 2 more Smart Citations
“…Yet, their three-category classification is based on a small sub-sample of their data, consisting of only 38 students. 10 The non-incentivized version of the Ellsberg urn experiment with five answer possibilities shows a somewhat smaller fraction of ambiguity neutral subjects compared to Butler et al (2013). The results for the subjects' willingness to pay for complementary temperature lottery tickets are qualitatively similar to Fox and Tversky (1995), although their average relative ambiguity premium is with 39% around twice as large as in our experiment that exhibits an average relative ambiguity premium of 20%.…”
Section: Aggregate Consistencymentioning
confidence: 54%
“…The two tasks to elicit ambiguity preferences are based on the works by Lauriola and Levin (2001), Chakravarty and Roy (2009) and Butler et al (2013). Since ambiguity preferences are closely related to risk preferences (Chakravarty and Roy, 2009), we also include an task to elicit risk preferences, similarly taken from Chakravarty and Roy (2009).…”
Section: Incentivized Tasksmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing literature has identified a positive relation between deliberative decision-making tendency and risk aversion. It has been shown that deliberative thinkers are more risk-aversive than intuitive thinkers, and that in risky and uncertain decision making environments deliberative processing is more likely to lead to conservative and risk-aversive decisions (Butler, Guiso, & Jappelli, 2014). Therefore, during creative idea selection, deliberative thinkers may focus on evaluating the potential risks of the available ideas.…”
Section: Introductionmentioning
confidence: 99%
“…And ambiguity aversion has predictive power for real life decisions (Ross et al 2012;Engle-Warnick et al 2011;Sutter et al 2013;Bianchi and Tallon 2014;Dimmock et al 2016a, b). However, the literature on the relationship between risk aversion and income 1 is much richer than the literature on the relationship between ambiguity aversion and income (Akay et al 2012;Butler et al 2014;Dimmock et al 2016b). The main reason for this gap in the literature is that until recently no tools were available to measure ambiguity attitudes in natural circumstances.…”
Section: Introductionmentioning
confidence: 99%